Exclusive optimization of Cs2AgBi0.75Sb0.25Br6-based solar cells using dual ETL with better photo transmission - Neupane, Kumar; Bhattarai, Sagar; Deka, Nitumoni; Alali, Ahmet Sait; Yousfi, Abderrahim; Saidani, Okba; Rahman, Md. Ferdous; Kumar, Abhinav; Karamti, Hanen (SPRINGERNATURE, 2025)
The current study discusses an eco-friendly, sustainable, lead-free, perovskite-based solar cell architecture that enhances photoconversion efficiency. We selected caesium silver bismuth Antimony bromide (Cs2AgBi0.75Sb0.25Br6) as the absorber material due to its non-toxic properties, remarkable thermal and chemical stability, and compatibility with cost-effective solution-processing techniques. The photovoltaic characteristics of the Cs2AgBi0.75Sb0.25Br6 -based device are examined using SCAPS-1D solar simulation software. Additionally, we analyze the output characteristics for optimal thickness-defect, IF defects, and Series-Shunt resistances to achieve optimized performance. The output PV parameters of a dual ETL-based PSC device having the structure of ITO/AZO/Mxene + TiO2/Cs2AgBi0.75Sb0.25Br6/V2O5/Ag achieve maximum fill factors of 90.21%, as well as an outstanding 22.11% PCE, surpassing the performance of its kind, which is a significant growth in designing the perovskite solar cell. It can be noted that the overall device efficiency increases with lesser defects and lower thickness in the carrier transport layers. The work provides a detailed analysis of the Caesium-based PSC, which can be effective in inorganic-based solar devices with semi-transparent characteristics.
Keywords: Solar cells (SCs); Cs2AgBi0.75Sb0.25Br6; Perovskite solar cell (PSC); SCAPS-1D software; DOUBLE PEROVSKITE; CS2AGBIBR6; EFFICIENCY; Engineering; Materials Science